Improving Early Speaking Skills through The Use of Picture-Words Cards Online in Early Childhood - Susyanti, Media; Surastina, Surastina; Sutrisno AB, Joko; Wiratno, Purna (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2020)
This study aims to determine the use of picture word cards online in improving the quality of early speaking skills learning and to determine the improvement of early speaking skills in early childhood group B Al Azhar 18 Bandar Lampung Kindergarten in academic year 2019/2020. This type of research is Classroom Action Research (CAR) which is carried out in collaboration with class B teachers. The research design used goes through four stages, namely planning, action, observation and reflection. The subjects of this study were 25 children consisting of 9 boys and 16 girls. The object of research is speaking skills. Data collection techniques using observation and documentation. The data analysis technique used is descriptive qualitative and quantitative. The results showed that early speaking skills could be improved using pictorial word cards for group B children at Al Azhar Kindergarten 18 Bandar Lampung in the academic year 2019/2020. The results of the increase in initial speaking skills before the action were 55.25% which were included in the poor criteria and in the first cycle as many as 73% which were included in the sufficient criteria, so that there was an increase of 17.75%. The results in Cycle II were 91% which were included in good criteria, so there was an increase of 18%.